2019
DOI: 10.3390/ijerph16173074
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Epigenetic Age in Response to Intensive Relaxing Training: A Pilot Study to Slow Down Biological Age

Abstract: DNA methylation (DNAm) is an emerging estimator of biological aging, i.e., the often-defined “epigenetic clock”, with a unique accuracy for chronological age estimation (DNAmAge). In this pilot longitudinal study, we examine the hypothesis that intensive relaxing training of 60 days in patients after myocardial infarction and in healthy subjects may influence leucocyte DNAmAge by turning back the epigenetic clock. Moreover, we compare DNAmAge with another mechanism of biological age, leucocyte telomere length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Only two works have been recently published on this topic. Firstly, Pavanello et al examined the hypothesis that an intensive relaxing training of 60 days may influence epigenetic age by turning back the epigenetic clock (Pavanello et al 2019) (Pavanello et al 2019). They observed a trend to a reduction in DNAm age (estimated with the model proposed by Zbiec-Piekarska et al (Zbieć-Piekarska et al 2015) after training in six healthy subjects, but the effect was not statistically significant (p = 0.053).…”
Section: Discussionmentioning
confidence: 99%
“…Only two works have been recently published on this topic. Firstly, Pavanello et al examined the hypothesis that an intensive relaxing training of 60 days may influence epigenetic age by turning back the epigenetic clock (Pavanello et al 2019) (Pavanello et al 2019). They observed a trend to a reduction in DNAm age (estimated with the model proposed by Zbiec-Piekarska et al (Zbieć-Piekarska et al 2015) after training in six healthy subjects, but the effect was not statistically significant (p = 0.053).…”
Section: Discussionmentioning
confidence: 99%
“…Twice-daily breathing exercises that elicit the Relaxation Response were prescribed for stress reduction. It was recently demonstrated that 60 days of relaxation practice designed to elicit the Relaxation Response, 20 minutes twice per day, could significantly reduce DNAmAge as measured by the Zbieć-Piekarska clock in their group of healthy participants (though not in their 'patient' group) (Pavanello et al, 2019). Almost a quarter of the DNAmAge CpG sites (85/353) are located in glucocorticoid response elements, pointing to a likely relationship between stress and accelerated aging.…”
Section: Introductionmentioning
confidence: 99%
“…The possible biophysical and molecular mechanisms underlying the heart–brain correlation have been discussed [ 12 ] and it has been shown [ 13 , 14 , 15 , 16 , 17 , 18 ] how the practice of relaxation response (RR) improves coronary blood flow, the heart contractility, and determines a favourable variation of inflammation molecules, stress hormones, neurotransmitters, aging markers, and circulating microRNAs, inducing an attenuation of the expression of some inflammatory genes in white blood cell precursors. Remarkably, the physical appearance of the subjects’ serum changes during RR [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%